Persistent Antibody Responses to SARS-CoV-2 Infection in Cancer Patients: A Single-Center Retrospective Observational Study - Agarwal, Amit; Baghmar, Saphalta; Qureshi, Suhail; Khurana, Aseem; Setia, Rasika; Khan, Maroof Ahmad; Barman, Purabi; Kapoor, Raj Kumar; Hasthavaram, Navneeth Reddy; Kumar, Ramesh; Singh, Navdeep; Sarin, Aditya; Handoo, Anil (Indian Journal of Medical and Paediatric Oncology, 2021)
Introduction There is limited literature available regarding the prevalence and durability of immune response to infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)/coronavirus disease 2019 (COVID-19) in cancer patients.Objective The aim of this study was to analyze the seroconversion rate in cancer patients recovered from SARS-CoV-2 infection.Materials and Methods We retrospectively analyzed antibody levels and seroconversion rates in serum samples from 135 cancer patients who had recovered from SARS-CoV-2 infection. Chemiluminescent immunoassay using Roche Cobas e801 analyzer (Roche Diagnostics, Rotkreuz, Switzerland) was performed to identify Pan Ig antibody against nucleocapsid antigen. Reports of first, third, and sixth month were analyzed. Seroconversion was also compared with health-care workers (HCW) of our institute who had recovered from COVID-19 infection.Results Seroconversion rate in cancer patients was 81.2% at 1 month, 95% at 3 months, and 94.6% at 6 months post reverse transcriptase–polymerase chain reaction positivity. There was no difference in seroconversion rate among different age groups, gender, comorbidities, severity of COVID-19 symptoms, cancer disease status, and treatment with chemotherapy. Seroconversion rate in cancer patients is comparable to HCW (90.4 vs. 96%, p = 0.82) and is durable.Conclusion Humoral response to COVID-19 infection in cancer patients is comparable to general population and sustained. Such responses suggest that cancer patients are likely to benefit from COVID-19 vaccination.
Keywords: COVID-19; SARS-CoV-2; anti-SARS-CoV-2-antibody; cancer; seroconversion; chemotherapy; India